Comparison of S gene mutations in patients with occult and chronic hepatitis B virus infection - Çakal, Bülent; Çavuş, Bilger; Atasoy, Alp; Altunok, Damla; Poda, Mehveş; Bulakçı, Mesut; Gülluoğlu, Mine; Demirci, Mehmet; Türker Şener, Leyla; Arslan, Aslı Berru; Arıkan, Muzaffer; Akyüz, Filiz (Elsevier B.V., 2022)
Background and aim: This study aimed to detect mutations in the HBV S gene and evaluate their relationship to occult hepatitis B virus (HBV) infection (OBI). Methods: The study included 32 patients with negative serum HBsAg and HBV DNA who underwent liver biopsy due to different clinical indications defined as the OBI group and 32 patients who underwent liver biopsy due to chronic hepatitis B (CHB) as the comparison group. The HBV S gene region was amplified by Nested PCR, and Sanger sequencing was performed. Results: At least one amino acid (aa) mutation was detected in the major hydrophilic region (MHR) of the HBV S gene in 14/32 (43.75%) of the patients with OBI and 8/32 (25.0%) with CHB. The genotype of all patients with OBI and CHB was HBV/D. Although 9 (28.1%) of the cases with OBI had sub-genotype HBV/D3, none of the patients with CHB had sub-genotype HBV/D3. Unlike patients with CHB, L15*, D33N, Q51P, V63F, L91I, P108S, T115I, P120L, T125M, Q129H, T189I, L216F, P217L mutations were detected in the HBV S gene in OBI cases. Also, P127T aa polymorphism was frequently detected. Mutation frequency in the HBV S gene in the major hydrophilic region (MHR) was higher in patients with OBI with sub-genotypes HBV/D3 and D2 than those with HBV/D1 and those with serotype HBV/ayw3 compared to those with HBV/ayw2 (p < 0.05). Conclusions: Sub-genotypic-specific mutation patterns were seen in the “a” determinant region and T helper cell epitopes of HBsAg, especially in the C-terminus domain; this may be associated with OBI.
Keywords: Occult HBV Infection; HBV S Gene; Immune Epitopes; Mutation; Sub-Genotype